2015
DOI: 10.1371/journal.pone.0116746
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance: The Major Contribution of Poor Governance and Corruption to This Growing Problem

Abstract: ObjectivesTo determine how important governmental, social, and economic factors are in driving antibiotic resistance compared to the factors usually considered the main driving factors—antibiotic usage and levels of economic development.DesignA retrospective multivariate analysis of the variation of antibiotic resistance in Europe in terms of human antibiotic usage, private health care expenditure, tertiary education, the level of economic advancement (per capita GDP), and quality of governance (corruption). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 27 publications
7
135
0
Order By: Relevance
“…Improving government effectiveness could be a vital step towards meeting UN Sustainable Development Goal 7 of ensuring access to modern energy for all. Our finding provides an example of the wide-ranging impact of institutions, complementing other examples such as the finding of Collignon et al [55] that poor governance contributes to the adverse public health outcome of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 76%
“…Improving government effectiveness could be a vital step towards meeting UN Sustainable Development Goal 7 of ensuring access to modern energy for all. Our finding provides an example of the wide-ranging impact of institutions, complementing other examples such as the finding of Collignon et al [55] that poor governance contributes to the adverse public health outcome of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 76%
“…120 On the other hand, it has been consistently shown that those areas where the usage is high, the resistance is widespread both in community and hospital settings. 7,121,122,123 Since the problem of emerging resistance is multifaceted, its prevention and control will require multiple, coordinated interventions by various parties. 119 At the hospital level; education and promotion of prudent use of antimicrobials, development and effective use of rapid and point of care diagnostic tests, devising effective surveillance systems for monitoring resistance and implementation of effective infection control programmes are essential parts of an antibiotic stewardship program.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…6 Poor governance and corruption have also been suggested to contribute to the levels of AMR in a given country. 7 …”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study by Bjerrum et al [10] it was discovered that national differences in prescription rates do not tend to mirror the prevalence of bacterial infections, but are related to national recommendations, treatment traditions and pharmaceutical marketing. Other contextual factors found to be important in the previous literature are type of health-care system [9], corruption [11,12] and a number of cultural factors [13,14], for example, risk aversion [15,16].…”
Section: Previous Researchmentioning
confidence: 99%